MANAGEMENT OF HUMAN RESOURCES IN THE QUALITY MANAGEMENT SYSTEM OF A TRANSPORT COMPANY - M. Maltseva (Вестник университета)
The article considers the role of the human factor in the quality management system of a transport company. Specific features of quality management of transport services are determined. Variants of stimulation and motivation of work are considered. Recommendations are given to improve the quality management system of the transport enterprise. The importance of assessing the efficiency of workers’ work, improving their skills and ensuring the organization’s commitment to increase the company’s competitiveness is underlined. The necessity and ways of involving the personnel in the process of ensuring the quality of transport services are substantiated.